Polymorphic borders. Issue 3 (3rd July 2017) - Burridge, Andrew; Gill, Nick; Kocher, Austin; Martin, Lauren
ABSTRACT: Polymorphic borders. Territory, Politics, Governance . Conceptualizing the respatialization, rescaling and mobilization of border work is a central problem in current borders research. Traditional and ubiquitous border concepts imply a coherent state power belied by much contemporary research. In this introduction to the special issue on 'Polyphorphic Borders' we suggest that not only do empirical studies of border work reveal a much more fragmented and chaotic world of bordering that is more guided by site- and agent-specific contingencies than by grand schemes, but also that representing borders as ubiquitous calls forth the state as coherent, monstrous, omnipotent and omniscient. Rather than being either strictly tied to the territorial margins of the states or ubiquitous throughout the entire territory of states, bordering takes on a variety of forms, agents, sites, practices and targets. We propose reconceptualizing borders as polymorphic, or taking on a multiplicity of mutually non-exclusive forms at the same time. In this introduction we propose the metaphor of polymorphic borders in order to account for the respatialization of border work beyond and within traditional borders in a way that avoids viewing borders as either lines, or everywhere. The articles that follow elaborate polymorphic borders through ethnographic investigations of border work at various sites and scales.